Novel role for carbamoyl phosphate synthetase 2 in cranial sensory circuit formation. Issue 33 (23rd November 2013) - Cox, Jane A.; LaMora, Angela; Johnson, Stephen L.; Voigt, Mark M.
Abstract: In zebrafish, cranial sensory circuits form by 4 days post‐fertilization. We used a forward genetic screen to identify genes involved in the formation of these circuits. In one mutant allele, sl23, axons arising from the epibranchial sensory ganglia do not form their stereotypical terminal fields in the hindbrain. These embryos also had small eyes and deformed jaws, suggesting a pleiotropic effect. Using positional cloning, a 20‐nucleotide deletion in the carbamoyl‐phosphate‐synthetase2‐aspartate‐transcarbamylase‐dihydroorotase ( cad ) gene was found. Injection of a CAD morpholino phenocopied the mutant and mutants were rescued by injection of cad RNA. Cad activity is required for pyrimidine biosynthesis, and thus is a prerequisite for nucleic acid production and UDP‐dependent protein glycosylation. Perturbation of nucleic acid biosynthesis can result in cell death. sl23 mutants did not exhibit elevated cell death, or gross morphological changes, in their hindbrains. To determine if defective protein glycosylation was involved in the aberrant targeting of sensory axons, we treated wild type embryos with tunicamycin, which blocks N‐linked protein glycosylation. Interference with glycosylation via tunicamycin treatment mimicked the sl23 phenotype. Loss of cad reveals a critical role for protein glycosylation in cranial sensory circuit formation.